Effects of Temperature on the Bioenergetics of the Marine Protozoans Gyrodinium dominans and Oxyrrhis marina - Calbet, Albert; Martínez, Rodrigo Andrés; Saiz, Enric; Alcaraz, Miquel (Frontiers in Marine Science, 2022)
We exposed Gyrodinium dominans and two strains of Oxyrrhis marina to temperatures well above (25°C) and below (12°C) their maintenance temperature (18°C) to study the mechanisms controlling the overall physiological response to thermal stress. As variables, we measured growth, ingestion, and respiration rates (this latter with and without food). The growth rates of O. marina strains plotted as a function of temperature showed maximum values at the maintenance temperature, as expected in a typical unimodal functional response. However, G. dominans showed similar growth rates at 12 and 18°C, and even a marked decrease in growth rates at 25°C, happened to be not significant. G. dominans ingestion rates were not significantly different at all temperatures (although apparently decreased at 25°C), whereas both O. marina strains showed higher ingestion rates at 18°C. The respiration rates of G. dominans were unaffected by temperature, but those of O. marina strains increased with temperature. The specific dynamic action (respiration increase produced by feeding activity) ranged from 2 to 20% of the daily carbon ingestion for all organisms investigated. The calculated energetic budget indicated that the responses to temperature were diverse, even between in strains of the same species. G. dominans maintained similar growth at all temperatures by balancing metabolic gains and losses. In O. marina strains, on the other hand, the decrease in growth rates at the lowest temperature was driven mainly by reduced ingestion rates. However, increased respiration seemed the primary factor affecting the decrease in growth rates at the highest temperature. These results are discussed in the light of previous studies and on its suitability to understand the response of wild organisms to fluctuations in temperature.